A new index of cortical plasticity induced by paired associative stimulation to describe cognitive status in aged healthy subjects - Loi, Nicola; Ginatempo, Francesca; Zeroual, Mohammed; Ventura, Lucia; Cano, Antonella; Oneto, Carmen; Ortu, Paola; Piras, Maria Rita; Deriu, Franca (Frontiers in Physiology, 2025)
IntroductionCortical plasticity is a key factor for cognitive skills, and paired associative stimulation (PAS) is useful to study it in humans. Currently, due to the number of non-responders to PAS and discrepancies in the post-PAS time-points assessed, a plasticity index describing PAS effects and correlating it to cognitive status is lacking. Therefore, this study investigated which PAS index better discriminates between responders (RRs) and non-responders (NRs) and correlates with cognitive status.MethodsSeventy-six healthy aged subjects (67.0 ± 7.2 y.o., 35 males) were enrolled. The Montreal Cognitive Assessment (MoCA), the Mini-Mental State Examination (MMSE), and the Addenbrooke’s Cognitive Assessment (ACER) were used to assess cognitive status. Motor-evoked potentials (MEPs) were recorded from the first dorsal interosseous muscle at baseline and after 0, 10, 20, and 30 min from PAS, pairing peripheral median nerve stimulation with a transcranial magnetic stimulation stimulus over the left primary motor cortex. MEP amplitude was used to calculate the grand average (GrA), which is the mostused PAS plasticity index, along with two newly introduced indexes: the curve concavity (CC) and the pre- vs. post-PAS difference (PPPD). CC described the curve shape of the PAS effects, while PPPD calculated the significant differences between the baseline and post-PAS MEP amplitude. ResultsCC demonstrated good consistency as PAS-plasticity index with high odds ratios and sensibility in the discrimination of responsiveness to PAS; PPPD had higher specificity in the identification of RRs. Only the MoCA score was significantly higher (p = 0.006) in RRs than in NRs when the two groups were discriminated according to CC, and it significantly correlated with CC (p = 0.013). DiscussionIn conclusion, CC may represent a potential PAS-plasticity index to describe the cortical plasticity and cognitive status in humans, with a possible practical application in patients with cognitive impairment.